Maria Madalena: luzes e sombras na urdidura de uma imagem - Quizzo, Dirce Socorro (2005)
The objective of this paper is to demonstrate that in the Christian occident the image of Maria Magdalen, a well-known biblical character underwent some changes throughout the centuries. The aim was to de-characterize the apostolic work carried out by women, and that contributed to build the identity of the female gender, marked by low self-esteem, and as a consequence, by weak empowerment. Aiming at recreating the path of the construction of this image, the author researched selected fundamental texts of Christianity, biblical literature, apocryphal literature as well as the patristic literature, using interpretation keys advocated by the feministic hermeneutics, which allows us to read gender as an analytic category of relationships built on the basis of culture. It was possible to ascertain that, in Maria Magdalen the female archetype was created, the biblical ideal that had to be transported to the concrete aspects of daily life, an apostle whole importance was minimized by the authors of the Canon.